Pentingnya Literasi Pencatatan Keuangan Secara Digital Bagi Para Pelaku UMKM - Ayu Dannisa Sarah Mudmainah; Kustiadi Basuki; Samsul Ode (Jurnal Pemberdayaan Nusantara, 2023)
Financial records are a problem faced by MSME actors, especially when applying for capital loans to financial institutions, there are still many cases today. This socialization was carried out as part of a community service program in the form of providing simple digital financial recording literacy, the aim of which is to provide knowledge and understanding of simple digital financial recording problems to MSME actors. The population in community service activities is MSME actors in the Sunter Agung Village with a sample of 20 MSME actors. The method used is lectures and practice of simple digital financial recording problems. by students of the University of 17 August 1945 Jakarta accompanied by their supervisor. Parameters for evaluating success in this activity used the Pre-Test and Post-Test questionnaires. The expected result is an increase in knowledge of simple financial recording for MSME actors and they can begin to practice it regularly.